2019
DOI: 10.3390/biom9120882
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesized ZnO-NPs from Morus indica Attenuates Methylglyoxal-Induced Protein Glycation and RBC Damage: In-Vitro, In-Vivo and Molecular Docking Study

Abstract: The development of advanced glycation end-products (AGEs) inhibitors is considered to have therapeutic potential in diabetic complications inhibiting the loss of the biomolecular function. In the present study, zinc oxide nanoparticles (ZnO-NPs) were synthesized from aqueous leaf extract of Morus indica and were characterized by various techniques such as ultraviolet (UV)-Vis spectroscopy, Powder X-Ray Diffraction (PXRD), Fourier Transform Infrared Spectroscopy (FT-IR), Scanning electron microscopy (SEM), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…It may be noted through the FT-IR spectrum of ZnO-NPs that functional groups present in plant extract had complexed well to form a metal oxide as indicated by the absence of major peaks between 600 and 400 cm −1 [ 2 , 5 , 6 ]. The results affirm that during the phyto-fabrication of ZnO-NPs, the metabolites in plant extract act as capping/stabilizing agents to form a metal oxide, which is also in agreement with the conclusions of other researchers [ 6 , 9 , 25 ].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It may be noted through the FT-IR spectrum of ZnO-NPs that functional groups present in plant extract had complexed well to form a metal oxide as indicated by the absence of major peaks between 600 and 400 cm −1 [ 2 , 5 , 6 ]. The results affirm that during the phyto-fabrication of ZnO-NPs, the metabolites in plant extract act as capping/stabilizing agents to form a metal oxide, which is also in agreement with the conclusions of other researchers [ 6 , 9 , 25 ].…”
Section: Resultssupporting
confidence: 92%
“…Further insight on the quantitative elemental analysis of ZnO-NPs through EDS revealed that the particles were of 88.11% purity ( Figure 4 B). Correspondingly, researchers have reported that the biosynthesis of ZnO-NPs from the extracts of plant materials exemplify better purity, which has been confirmed by XRD, SEM, and EDS analysis [ 6 , 9 , 14 , 16 ]. The FT-IR spectroscopic analysis of ZnO-NPs and aqueous plant extract helped to recognize the functional groups that were responsible for the phyto-fabrication of the nanoparticles during the reduction and stabilization.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Biochemical shifts in RBC are accompanied by morphological changes. Treating RBCs with MG in vitro leads to the transformation of normal biconcave cells into echinocytic ones [180]. In RBCs obtained from the blood of diabetic patients, hypochromia and anisopoikilocytosis (the spread of RBCs by size and shape) were observed [181].…”
Section: Relationship Of Carbonyl Stress With Oxidative and Nitrosatimentioning
confidence: 99%
“…We can assume that dietary polyphenols will be effective in fighting the carbonyl stress in RBCs. Zinc oxide nanoparticles (ZnO-NP) synthesized from an aqueous extract of Morus indica leaves were also reported as promising pharmacological agents with therapeutic potential at diabetic sequela [180].…”
Section: Pharmacological Interventions and Future Perspectivesmentioning
confidence: 99%